Non-parenchymal hepatic cell lipotoxicity and the coordinated progression of non-alcoholic fatty liver disease and atherosclerosis. Issue 5 (October 2018) - Peters, Kia M.; Wilson, Rachel B.; Borradaile, Nica M.
Abstract : Purpose of review: Non-alcoholic fatty liver disease (NAFLD) appears to be independently associated with the development of atherosclerosis. The biological mechanisms underlying this association are complex, and likely involve liver-resident cell types other than hepatocytes. Thus, we review recent evidence that non-parenchymal hepatic cell responses to lipid excess contribute to the pathogenesis of both NAFLD and atherosclerosis. Recent findings: Significant independent associations between NAFLD and atherosclerosis have been identified through cross-sectional studies and meta-analyses. Mechanistic studies in cell cultures and in rodent models suggest that liver-resident macrophages, activated hepatic stellate cells (HSC) and liver sinusoidal endothelial cells (LSEC) mount lipotoxic responses under NAFLD conditions which can contribute to the progression of both NAFLD and atherosclerosis. Summary: Non-parenchymal hepatic cell types exhibit some similarity in their responses to lipid excess, and in their pathogenic mechanisms, which likely contribute to the coordinated progression of NAFLD and atherosclerosis. In response to lipotoxic conditions, macrophages, Kupffer cells and HSC initiate robust inflammatory responses, whereas LSEC generate excess reactive oxygen species (ROS). The extent to which inflammatory cytokines and ROS produced by non-parenchymal cells contribute to the progression of both NAFLD and atherosclerosis warrants further investigation.